Validity of p-LDH/HRP2-Based Rapid Diagnostic Test for the Diagnosis of Malaria on Pregnant Women in Maluku - Vebiyanti Vebiyanti; Elsa Herdiana Murhandarwati; Bambang Udji Jokorianto (Tropical Medicine Journal, 2013)
ABSTRACTIntroduction: Pregnant women are one of the groups at risk for infection by the malaria parasites in endemic areas. The dangerous impacts of malaria in pregnancy are anemia and severe malaria that can cause death for mother, fetus and newborn. Clinical symptoms that are likely to be not typical until asymptomatic in pregnancy are one of the obstacles on diagnosing malaria in pregnancy in endemic areas. p-LDH/HRP2-RDT (Pf/Pan) is one of the WHO recommended RDT product on round 1-4 and has been used in Maluku. This tool is able to detect antigens of the Plasmodium metabolism results in peripheral blood so that it is regarded to be more sensitive than microscopic examination. The use of p-LDH and HRP2-RDT (Pf/Pan) for the detection of P. falciparum HRP-2 antigen and P. vivax, P.malariae, P.ovale p-LDH antigen have not been previously evaluated in the Province of Maluku.Objectives: To evaluate the validity of p-LDH/HRP2-RDT (Pf/Pan) compared with microscopic examination and nested Polymerase Chain Reaction (PCR) as the gold standard for the diagnosis of malaria in pregnancy in Maluku.Methods: This was a cross-sectional study using a diagnostic test of malaria in pregnant women. The study was conducted in Ambon City health center, Savana Jaya Buru Island health center and Haulussy Ambon Local Hospital. Sample data, the data of pregnancy, RDT results and microscopic results on the field were recorded in the questionnaire. Nested PCR examination was conducted at the Laboratory of Parasitology, Faculty of Medicine, Universitas Gadjah Mada as well as second reading for microscopic examinationResults: The results showed that p-LDH/HRP2-RDT  (Pf/Pan) had the same sensitivity with micoscopic of 11%, a specificity of 100% higher than microscopic 96% compared with nested PCR as the gold standard, p-LDH/HRP2-RDT (Pf/Pan) had PPV and NPV of 100% and 98% compared with nested PCR as the gold standard. p-LDH/HRP2-RDT (Pf/Pan) sensitivity was 80% compared to the microscopic examination.Conclusion: diagnostic malaria in pregnancy in Maluku with p-LDH/HRP2-RDT (Pf/Pan) was less sensitive than nested PCR and microscopic.Keywords: Malaria, pregnant woman, diagnostic test, validity, p-LDH/HRP2 Rapid Diagnostic Test (RDT) (Pf/Pan)